Um “estádio primitivo de cultura”: a perspectiva orientalista de Adolfo Coelho sobre os ciganos de Portugal (1892) (Altre Modernità, 2019)
This paper departs from Francisco Adolfo Coelho’s text on Os ciganos de Portugal – com um estudo sobre o calão [The Gypsies of Portugal – with a study of jargon use], which was produced within the 10th International Congress of Orientalists. This event would have taken place in Lisbon in 1892 had it not been cancelled. Our purpose is to examine how Adolfo Coelho’s discourse about the gypsies, which is in line with analogous studies produced in the academic context of the time, relates to some of the arguments developed by Edward W. Said in his Orientalism (1978). This happens either by expanding on the exotic (or exoticized) nature of the gypsies or via a moral, historical and cultural narrative that tends to be selective and through which the facts that more conveniently serve the author are emphasized. In light of Said’s thesis and others that followed, including the analysis of attitudes towards minorities or even the inhabitants of a country, it will be possible to put forward Adolfo Coelho’s study, which is mainly linguistic and ethnographic-oriented, as an example of a construction of the West. This West emerges with self-invested authority to unilaterally intervene in the image and identity of the Other, in this case the gypsies of Portugal